ANALISIS ALGORITMA C4.5 UNTUK MENENTUKAN FAKTOR PEMBELIAN SEPEDA BEKAS PADA TOKO SEPEDA BATAM - Harman, Rika; Amrizal, Amrizal (Computer Based Information System Journal, 2021)
The large number of bicycle enthusiasts has made the demand for bicycles increasing, not only new bikes but also used bikes. With the sale, of course, there are also purchases of used bikes, which before buying, of course, you must know the buying factor for used bikes to be sold. However, as long as this business is running, there has never been an in-depth analysis of factors affecting the purchase of used bikes for sale or making a reference or standard regarding the factors that affect the purchase of used bikes for sale. Thus, many customers who have bought used bicycles have complained about used bikes that have been purchased after using them for some time. With this problem, the researcher wants to provide a solution to the problems faced by motorcycle shops so far, namely by analyzing the data on used bikes that will be sold using one of the methods in the datamining technique, namely the C4.5 algorithm. The following are the results of the research: a). If the bicycle wheels are bent, the bicycle will not be purchased; b). If the bicycle rims are not bent or normal and the bicycle komstir is rocking then the bicycle will not be purchased; and c). If the bicycle wheels are not bent or normal and the bike is not rocking or steady, the bicycle will be purchased.